2022
DOI: 10.3390/cancers14020284
|View full text |Cite
|
Sign up to set email alerts
|

Risk of New Primary Cancer in Patients with Posterior Uveal Melanoma: A National Cohort Study

Abstract: Background: Studies on the risk of new primary cancer in patients with posterior uveal melanoma (UM) have produced conflicting results, and the role of socioeconomic status (SES) is unknown. The purpose of this population-based matched cohort study was to determine the risk of new primary cancer following the diagnosis of posterior UM. Methods: 2179 patients with posterior UM 1968–2016 and 22,717 matched controls without cancer were included. Incidence and time-dependent hazard ratio (HR) of new primary cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 29 publications
1
7
2
Order By: Relevance
“…Compared to the recently published study from Denmark (Bagger et al, 2022), our material had a higher proportion of patients in stage I (26% vs. 17%), and lower proportions in stage III/IV (23% vs. 27%) and unspecified (0.1% vs. 4%). Inclusion to our patient cohort started two decades later than the Danish study.…”
Section: Icd-10contrasting
confidence: 74%
See 4 more Smart Citations
“…Compared to the recently published study from Denmark (Bagger et al, 2022), our material had a higher proportion of patients in stage I (26% vs. 17%), and lower proportions in stage III/IV (23% vs. 27%) and unspecified (0.1% vs. 4%). Inclusion to our patient cohort started two decades later than the Danish study.…”
Section: Icd-10contrasting
confidence: 74%
“…Compared with non-cancer controls, cancer survivors undergo more screening examinations during surveillance (Corkum et al, 2013) and knowledge about malignant comorbidity in UM patients may increase awareness in medical surveillance after UM that can reveal additional malignancies. To date, however, there are no evidence-based guidelines for surveillance of new primary cancer during follow-up of UM patients (Bagger et al, 2022). Although neither the Swedish nor the Danish study found significantly increased risk for any specific cer type, the most frequent additional cancers were of breast, prostate, colorectum, lung and skin, which also was seen in our data.…”
Section: Icd-10contrasting
confidence: 71%
See 3 more Smart Citations